Dynamic braking performance of a low-mass prototype vehicle under different speeds and loads - Istana, Budi; Ridwan, Abrar; Sitompul, Izazul Kafitra (Jurnal Polimesin, 2025)
Dynamic braking performance is well understood in conventional vehicles, but its characteristics in ultra-lightweight, energy-efficient prototype vehicles remain poorly documented, despite their growing role in energy efficiency competitions and urban mobility concepts. This study experimentally investigated stop braking performance under varying vehicle speeds and masses in a low-mass prototype vehicle (V1.0). Tests were conducted at four speed levels (10, 20, 30, and 40 km/h) and two mass configurations (135 kg and 165 kg), with each scenario repeated five times on a flat 100 m track. With an increase in speed from 30 to 40 km/h, the 135-kg configuration showed increases in braking distance of 11.14 m (133%), braking time of 1.92 s (47%), and disc pad temperature of 0.66 °C (1.5%). The 165-kg configuration showed corresponding increases of 14.21 m (152%), 3.02 s (75%), and 1.40 °C (3.3%). Across the full test range, increasing speed from 10 km/h to 40 km/h for the 135-kg configuration increased braking distance from 1.78 m to 19.5 m (+995%) and braking time from 1.63 s to 5.04 s (+209%). Increasing mass from 135 kg to 165 kg at 30 km/h increased braking distance by 0.97 m (11.6%) and braking time by 0.59 s (17.3%). Disc pad temperatures remained within a safe range, rising only from 41.1 °C to 42.5 °C (+3.4%) across the tested speeds. These quantitative findings provide critical data for optimizing braking system design in lightweight, energy-efficient prototypes, ensuring operational safety under various load and speed conditions.